EFFECTS OF INTEREST RATE ON PROFITABILITY OF LISTED DEPOSITE MONEY BANKS IN NIGERIA - Joseph Olorunfemi Akande (Gusau Journal of Accounting and Finance, 2025)
Fluctuations in interest rates remain a critical challenge affecting the profitability of listed deposit money banks in Nigeria. This study investigates the relationship between interest rates and banks profitability, focusing on Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM) among 10 listed deposit money banks from 2013 to 2022. Employing a panel regression approach, the study analyses secondary data from annual financial reports and regulatory sources to assess how interest rate movements influence banking performance. Preliminary findings indicate that interest rate fluctuations impact profitability, but the extent and direction of these effects vary across different financial indicators. While some banks benefit from higher interest rates through improved margins, others experience increased funding costs, reduced loan disbursement, and higher default risks. The study acknowledges that the final results are yet to be fully established, emphasizing the need for a nuanced approach to interest rate management. Given the evolving financial landscape, the study highlights the importance of risk-adjusted pricing models and hedging strategies to mitigate adverse effects. Additionally, regulatory policies that stabilize interest rates could help banks maintain profitability and sustain economic growth. The study's insights contribute to ongoing discussions on optimizing financial performance in Nigeria’s banking sector.